LA INCORPORACIÓN TECNOLÓGICA, MEDIANTE LA PROPUESTA DEL MODELO DE ASESORAMIENTO TECNOLÓGICO MULTIDISCIPLINARIO - Cerón, Marco Tulio; Flores, Verónica; de León, Verónica; González, Manuel (European Scientific Journal, ESJ, 2014)
One of the main problems that companies face to generate competitive advantage is to integrate their production technology suitable for this purpose. In this paper a Multidisciplinary Model of Technology Assessment (MATM) that responds to the aforementioned need is proposed. This model will serve to advise companies that do not have an area of research and development (R & D). Through MATM will advise the organization with the proper integration of new technology and give the advice required by a technological network. The MATM, help the company to have a proposal that will be useful for making decisions regarding the incorporation, purchase, commissioning and maintenance of technological equipment..